Α7 Nicotinic Acetylcholine Receptor Stimulation Attenuates Neuroinflammation through JAK2-STAT3 Activation in Murine Models of Intracerebral Hemorrhage. (26th April 2017) - Krafft, Paul R.; McBride, Devin; Rolland, William B.; Lekic, Tim; Flores, Jerry J.; Zhang, John H.
Abstract : Accounting for high mortality and morbidity rates, intracerebral hemorrhage (ICH) remains one of the most detrimental stroke subtypes lacking a specific therapy. Neuroinflammation contributes to ICH-induced brain injury and is associated with unfavorable outcomes. This study aimed to evaluate whether α 7 nicotinic acetylcholine receptor ( α 7nAChR) stimulation ameliorates neuroinflammation after ICH. Male CD-1 mice and Sprague-Dawley were subjected to intracerebral injection of autologous blood or bacterial collagenase. ICH animals received either α 7nAChR agonist PHA-543613 alone or combined with α 7nAChR antagonist methyllycaconitine (MLA) or Janus kinase 2 (JAK2) antagonist AG490. Neurobehavioral deficits were evaluated at 24 hours, 72 hours, and 10 weeks after ICH induction. Perihematomal expressions of JAK2, signal transducer and activator of transcription 3 (STAT3), tumor necrosis factor- α (TNF- α ), and myeloperoxidase (MPO) were quantified via Western blot. Histologic volumetric analysis of brain tissues was conducted after 10 weeks following ICH induction. PHA-543613 improved short-term neurobehavioral (sensorimotor) deficits and increased activated perihematomal JAK2 and STAT3 expressions while decreasing TNF- α and MPO expressions after ICH. MLA reversed these treatment effects. PHA-543613 also improved long-term neurobehavioral (sensorimotor, learning, and memory) deficits and ameliorated brain atrophy after ICH. These treatment effects were reduced by AG490. α 7nAChR stimulation reduced neuroinflammation via activation of the JAK2-STAT3 pathway, thereby ameliorating the short- and long-term sequelae after ICH.